Rekonstruksi Etika Profesi Penegak Hukum dalam Penanganan Korupsi Berbasis Teknologi Digital Perspektif Integritas, Akuntabilitas, dan Keadilan Siber - Robert Sangkala; Ida Komala; Satria Ari Wibowo; Roif Roif; ⁠Ali Asari; Windi Setiawan; Firman Adi Candra (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
Corruption remains one of the most significant challenges to the rule of law in Indonesia. Rapid advances in digital technology have transformed criminal behavior, evidentiary mechanisms, and public communication surrounding law enforcement processes. At the same time, the widespread use of social media, Artificial Intelligence (AI), digital data analytics, and electronic law enforcement systems has created both opportunities and ethical challenges for law enforcement professionals. This study aims to examine the urgency of reconstructing professional ethics for law enforcement officers in handling corruption cases within the digital environment and to formulate an ethical framework capable of preserving integrity, accountability, independence, and cyber justice. This research employs a normative legal research method using statutory, conceptual, case, and comparative approaches. Legal materials were collected through an extensive literature review of legislation, judicial decisions, professional codes of ethics, and relevant national and international scholarly publications. The findings indicate that the digital transformation of law enforcement has not been accompanied by adequate ethical reforms capable of addressing the implications of digital technology, public pressure through social media, Artificial Intelligence, and the spread of digital misinformation. These developments have the potential to undermine institutional independence and weaken public trust in the justice system. Consequently, this study proposes a reconstruction of professional ethics that incorporates digital integrity, algorithmic accountability, transparency in technological utilization, human rights protection, and digital governance-based ethical oversight as fundamental principles for modern, accountable, and equitable law enforcement.